EXPLORING DENTAL ASSISTANTS’ EXPERIENCES WITH FOUR-HANDED DENTISTRY IN SAUDI ARABIA: A QUALITATIVE STUDY - Ahmed Hamed Alanazi, Alzahrani, Saad Ali Abdullah, Al Dossarie, Mohammed Salih Hussain Alghamdi, Waleed Saad, Refaan Salem Al Hamry (Chelonian Research Foundation, 2022)
Four-handed dentistry, defined as operators working cooperatively with dental assistants using four hands simultaneously in the oral cavity, is increasingly utilized to enhance efficiency, ergonomics, and quality in dental care delivery. However, perspectives regarding experiences with four-handed clinical techniques among dental assistants are lacking in Saudi Arabia. This qualitative study aimed to address this gap by conducting semi-structured interviews with 15 dental assistants practicing in Riyadh regarding their experiences with and attitudes toward four-handed dentistry. Transcripts were analyzed using an inductive, thematic approach. Participants viewed four-handed dentistry positively as improving time management, efficiency, ergonomics, and teamwork. However, most reported receiving insufficient clinical training on cooperative four-handed techniques during dental assistant education. Key challenges highlighted included maintaining proper infection control with shared workspace, ineffective communication and coordination with dentists, and anxieties when assisting with new advanced procedures. Recommendations encompassed additional clinical education, development of cooperative four-handed protocols, and enhanced communication strategies. Findings provide important insights that can inform continued optimization of four-handed dentistry implementation in Saudi Arabia to enhance dental team productivity, ergonomics, infection control, communication, and quality of care delivery.